Insight Into Mosquito GnRH-Related Neuropeptide Receptor Specificity Revealed Through Analysis of Naturally Occurring and Synthetic Analogs of This Neuropeptide Family - Wahedi, Azizia; Gäde, Gerd; Paluzzi, Jean-Paul (Frontiers in Endocrinology, 2019)
Adipokinetic hormone (AKH), corazonin (CRZ) and the AKH/CRZ-related peptide (ACP) are neuropeptides considered homologous to the vertebrate gonadotropin-releasing hormone (GnRH). All three Aedes aegypti GnRH-related neuropeptide receptors have been characterized and functionally deorphanized. Individually they exhibit high specificity for their native ligands, prompting us to investigate the contribution of ligand structures in conferring receptor specificity for two of these receptors. Here, we designed a series of analogs based on the native ACP sequence and screened them using a heterologous system to identify critical residues required for ACP receptor (ACPR) activation. Analogs lacking the carboxy-terminal amidation, replacing aromatics, as well as truncated analogs were either completely inactive or had very low activities on ACPR. The polar threonine (position 3) and the blocked amino-terminal pyroglutamate are also critical, whereas ACP analogs with alanine substitutions at position 2 (valine), 5 (serine), 6 (arginine) and 7 (aspartate) were less detrimental including the substitution of charged residues. Replacing asparagine (position 9) with an alanine resulted in a 5-fold more active analog. A naturally-occurring ACP analog, with a conserved substitution in position two, was well tolerated yet displayed significantly reduced activity compared to the native mosquito ACP peptide. Chain length contributes to ligand selectivity in this system, since the endogenous octapeptide Aedae-AKH does not activate the ACPR whereas AKH decapeptides show low albeit significant activity. Similarly, we utilized this in vitro heterologous assay approach against an A. aegypti AKH receptor (AKHR-IA) testing carefully selected naturally-occurring AKH analogs from other insects to determine how substitutions of specific residues in the AKH ligand influence AKHR-IA activation. AKH analogs having single substitutions compared to Aedae-AKH revealed position 7 (either serine or asparagine) was well tolerated or had slightly improved activation whereas changes to position 6 (proline) compromised receptor activation by nearly ten-fold. Substitution of position 3 (threonine) or analogs with combinations of substitutions were quite detrimental with a significant decrease in AKHR-IA activation. Collectively, these results advance our understanding of how two GnRH-related systems in A. aegypti sharing the most recent evolutionary origin sustain independence of function and signaling despite their relatively high degree of ligand and receptor homology.